PERANCANGAN APLIKASI SISTEM PAKAR UNTUK MENDIAGNOSIS PENYAKIT KULIT PADA KUCING DENGAN MENGUNAKAN METODE BAYESIAN PROBABILITY - Michael Antoni; Chairisni Lubis; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
This application created to diagnose skin diseases on cat using Bayesian Probability method which user have to input sympthoms that they pet feel to the application. This application can also give information about the diseases that this application cover. The disaeser are Seborrhea, Malassezia, Ringworm, Scabies, Psoroptes, Demodecosis, Acutemoist Dhermatitis, Atopic Dhermatitis, dan Acnespot. Based on the test result Bayesian Probability give accuracy up to 95.55%. Key wordspenyakit kulit, kucing, bayesian probability, sistem pakar